Borrelidin Induces the Unfolded Protein Response in Oral Cancer Cells and Chop-Dependent Apoptosis - Sidhu, Alpa (2015)
Oral squamous cell carcinoma (OSCC) is the most common cancer affecting the oral cavity, and US clinics will register about 30,000 new patients in 2015. Current treatment modalities include chemotherapy, surgery, and radiotherapy, which often result in astonishing disfigurement. Cancers of the head and neck display enhanced levels of glucose-regulated proteins and translation initiation factors associated with endoplasmic reticulum (ER) stress and the unfolded protein response (UPR). Previous work demonstrated that chemically enforced UPR could overwhelm these adaptive features and selectively kill malignant cells. The threonyl-tRNA synthetase (ThRS) inhibitor borrelidin and two congeners were discovered in a cell-based chemical genomic screen. Borrelidin increased XBP1 splicing and led to accumulation of phosphorylated eIF2α and UPR-associated genes, prior to death in panel of OSCC cells. Murine embryonic fibroblasts (MEFs) null for GCN2 and PERK were less able to accumulate UPR markers and were resistant to borrelidin. This study demonstrates that UPR induction is a feature of ThRS inhibition and adds to a growing body of literature suggesting ThRS inhibitors might selectively target cancer cells.